Meningkatkan Nilai Tambah Tomat Dengan Pelatihan Mengolah Tomat Segar Menjadi Saus Tomat Di Desa Gunung Bahgie - Askura Nikmah; Anna Permatasari Kamarudin; Masri Ramadhan; Bambang Surahman; Abdul Jalil; Rahma Diana; Rizsky Wan Purnama; Sabri Sabri (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The people of Mpunt Bahgie have the majority of their livehood as farmers, although tomatoes are not the dominant crop. During the tomatoe harvest period, the price of tomatioes will decrease. One way to ensure prices are stable is to process tehm into other, more durable products. Processing fresh tomatoes into tomato sauce is one way to use fresh tomatoes when prices are cheap. Tomato sauce products are also a way for people to increase their income and open new businesses. Tha aim of this community service is to provide knowledge and skills about processing fresh tomatoes into tomato sauce. The method used is by delivering material in the fform of lectures, counseling and demonstrations. A total of 1 partners who are housewives have participated in this program. The final results of the Pre Test and Post Test show that there has been a significant increase in Partners, especially in the knowledge of choosing ‘Know’ regarding processing, namely Partners know hoe to overcome falling prices during harvest from 83 to 100%; partners know that tomatoe sauce processing can be turned into business from 72% to 100%; partners know that tomato can be  processed into other products that are more durable from 55% to 100%; Partners knows how to make tomatosauce ffrom 28% to 100%. Meanwhile, the results of the assessment evaluation showed that 100% of Partners stated ‘Strongly Agree’ with the agenda the program implemented is useful; satisfied with the program implemented; and are interested in taking part in the program iff it is held at the same time another time. A series of core activities shows that training and delivery of material can provide knowledge and be easily accepted by Partners